Factors contributingto creativity among youth: a review - Tiraieyari, Neda; Hamzah, Azimi; Joorabchi, Toktam Namayandeh (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Youth have a critical role to play in every country. Hence it is important to preparing youth with appropriate competencies. Creativity is becoming increasingly important for our society. It empowers young people with the notion that they can translate their goals into tangible reality and also in order for youth to be prepared to work in partnership with adults, they need to develop and enhance their creativity. It contributes to economic prosperity as well as to social and individual wellbeing. This article reviews factors that may contribute to creativity among youth. A model developed based on review of possible determinants of creativity. Results of the study would help policy makers to give greater focus on the factors affecting creativity among youth. Thus the scope of youth activities, budget allocation, staff training, educational approach and goal would be better defined by taking cognizance of the results from this study.